Study of the clinical profile and treatment outcome of pulmonary and extrapulmonary tuberculosis patients coming to respiratory medicine OPD - Mani S., Thamil; Deshmukh, Hafis; Jadhav, Sunil; Deshmukh, Ashish; Kasat, Shivprasad; S., Thritia; Roy, Arya (International Journal of Research in Medical Sciences, 2023)
Background: The major risk factors for development of tuberculosis are extremes of age, malnutrition, overcrowding and immune deficient states like AIDS, diabetes mellitus, measles, whooping cough and leukaemia. Chronic malaria and worm infestation are less important risk factors. Tobacco smoking, high alcohol consumption, corticosteroid therapy and immunosuppressive drug therapy reduce body defences there by increasing the susceptibility to tuberculous infection. This study was undertaken to analyse the various clinical presentations in patients with pulmonary tuberculosis and extra pulmonary tuberculosis. Methods: This was a retrospective study of patients from October 2020 to September 2022 (2 years). Data collected from 300 patients who were diagnosed with pulmonary and extrapulmonary tuberculosis visited. The subjects were divided into subjects who had pulmonary TB (PTB), and who had extrapulmonary TB (EPTB). Results: The most common systemic disorders accompanying EPTB were DM (n=11; 8.8%) and chronic renal failure (n=8; 6.4%); while DM (n=16; 9.1%) and chronic obstructive pulmonary disease (n=13; 7.4%) were those detected frequently in PTB group. Conclusions: Present study showed higher percentage of males and greater predominance of pulmonary TB. It is also observed high percentage extrapulmonary TB. High percentage of positive treatment outcomes with fewer relapses and failures was observed in this study. A high positive treatment outcome noted may be attributed to the availability of specialist doctors and diagnostic facilities in the tertiary care centre.